Nordic Innovation Monitor 2009 (Copenhagen : Nordic Council of Ministers, 2009)
At the 26 and 27 of February 2009, the second Nordic Globalisation Forum will take place in Iceland. The Forum this year will focus on climate, energy and innovation. The Nordic Innovation Monitor will be presented for the first time ever at the Globalization Forum 2009. The Nordic Innovation Monitor exists in a short and a longer version. This is the full version that gives an in depth analysis of the innovation performance of the Nordic countries compared with leading countries in the world and the frameworks that exists in the individual countries. It allows for a fact based policy, and for learning from those countries in the world that shape the best conditions for innovation. It also allows for a more in depth analysis of each country. You will find the short version at www.norden.org.